2010
DOI: 10.1111/j.1742-7843.2010.00622.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled 1,8-Cineole Reduces Inflammatory Parameters in Airways of Ovalbumin-Challenged Guinea Pigs

Abstract: Eucalyptol, also known as 1,8-cineole, is a monoterpene traditionally used to treat respiratory disorders due to its secretolytic properties. In addition to its myorelaxant effects, it also has anti-inflammatory actions in vitro. In this study, we aimed to evaluate the efficacy of acute treatment with 1,8-cineole on reducing airway inflammatory parameters. Ovalbumin (OVA)-sensitized guinea pigs were submitted to antigenic challenge (OVA) with or without pre-treatment with a single dose of 1,8-cineole administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 24 publications
1
44
0
Order By: Relevance
“…Other monoterpenes have been reported to possess antiinflammatory activity in animal models (Bastos et al, 2011;Guimarães et al, 2012;Peana et al, 2002). However, both the anti-inflammatory action in vivo and cicatrizing activity of thymol are still not demonstrated.…”
Section: Introductionmentioning
confidence: 95%
“…Other monoterpenes have been reported to possess antiinflammatory activity in animal models (Bastos et al, 2011;Guimarães et al, 2012;Peana et al, 2002). However, both the anti-inflammatory action in vivo and cicatrizing activity of thymol are still not demonstrated.…”
Section: Introductionmentioning
confidence: 95%
“…1.8-Cineole strongly inhibited TNF-α and IL-1β level controlling airway mucus hypersecretion in asthma. 15) It also reduced the production of cytokines such as leukotriene B4 (LTB4) and prostaglandin E2 (PGE2) in human monocytes obtained from asthma patients. 13) However, the literature contains very little experimental data on how 1.8-cineole affects human epithelial cells stimulated by allergens such as HDMs.…”
mentioning
confidence: 99%
“…A possible pathway for this explanation may include the olfactory system. Autonomic nervous system is affected by odorants, thus inhalation of essential oil is direct actions on the autonomic nervous system via olfactory system [19, 20]. Recent study has shown that olfactory stimulation with lavender essential oil and its active component, linalool reduced the sympathetic nerve activity in rats [21].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 1,8-cineole was found to reduce cytokines that cause inflammation in guinea pigs [20], and to significantly reduce edema and CRP at sites of inflammation throughout the entire body [26]. These studies prompted us to hypothesize that eucalyptus oil would reduce pain following TKR by lessening inflammatory reactions.…”
Section: Discussionmentioning
confidence: 99%